Becoming the gospel: Paul, participation, and mission - Gorman, Michael J. (The Gospel and our culture series, 2015)
Invitation: Becoming the gospel -- Paul and the mission of God -- Reading Paul missionally -- Becoming the gospel of faith(fulness), love, and hope: 1 Thessalonians -- Becoming and telling the story of Christ: Philippians -- Becoming the gospel of peace (I): overview -- Becoming the gospel of peace (II): Ephesians -- Becoming the justice of God: 1 & 2 Corinthians -- Becoming the gospel of God's justice/righteousness and glory: missional theosis in Romans -- Final reflections: Becoming the gospel (reprise)